The Use of Cue Card in Cooperative Learning for Teaching Vocabulary - Parmi, Parmi (ELT Forum: Journal of English Language Teaching, 2019)
Vocabulary is the basic of English that is very important and difficult to master. Vocabulary will help students to master the four skills of language. Therefore, teacher have to make creative and interesting a way for teaching vocabulary.This study concern about how cue card and cooperative learning is used for teaching vocabulary. This study focused on theuse cue card as learning media and cooperative learning as learning method. The subject of this study was seven grade student of SMP N 41 Semarang. The aim of this study was to describe the implementation of cue card with cooperative learning in teaching vocabulary to the students in the classroom. This study was a qualitative case research. The observation, questionnaire, interview, and document analysis was used to collect the data. The questionnaire was given at the end of the study. The observation sheet used to monitor the students and teacher?s activities during the teaching learning process. The intrview was done at the end of the meeting.Based on the result, the researcher concluded that the use of cue card for teaching English vocabulary is interesting, effective, efficient, and arffordable. In addition, cooperative learning was helpfull to increase the student?s confidence.   Keywords: Cue Card, Cooperative Learning, English Vocabulary